PEDAGOGICAL CONDITIONS OF PROFESSIONAL TRAINING OF FUTURE SPECIALISTS IN THE FIELD OF PHYSICAL CULTURE AND SPORT IN HIGHER EDUCATION INSTITUTIONS (Physical Culture and Sport: Scientific Perspective, 2022)
The article analyzes and considers the problem of professional training of future specialists in the field of physical culture and sports in higher education institutions based on the use of competence approach. The method of professional training of future specialists in the field of physical culture and sports in higher education institutions is determined and substantiated, which consists in the introduction of a competency-based approach and modular learning technologies.The new strategy of modernization of educational content, pragmatic and humanistic orientation of the educational process, change of educational paradigm significantly changed the requirements for the level of training of graduates and put pedagogical science in front of the need to rethink the goals, objectives and methods of education in our country.The aim of the article is to determine and substantiate the methodology of professional training of future specialists in the field of physical culture and sports in higher education institutions, which is to introduce a competency-based approach and modular learning technologies.In the process of writing the article, the main provisions of the competence approach in the process of professional training of future specialists in the field of physical culture and sports were considered; the main directions of using the competence approach in the process of professional training are analyzed; the method of professional training of applicants in a higher education institution, which consists in the introduction of a competency-based approach and modular learning technologies, is substantiated.
Keywords: professional training; physical culture; sports; competence approach